INVESTIGATION OF ACCURATE METHOD IN 3-D POSITION USING CORS-NET IN ISTANBUL - GUMUS, KUTALMIS; CELIK, CAHIT TAGI; ERKAYA, HALIL (Boletim de Ciências Geodésicas, 2012)
In this study, for Istanbul, there are two Cors Networks (Cors-TR, Iski Cors) providing Virtual Reference Station (VRS), and Flachen Korrektur Parameter (FKP), corrections to rover receiver for determining 3-D positions in real time by Global Positioning System (GPS). To determine which method (or technique) provides accurate method for position fixing, a test network consisting of 49 stations was set up in Yildiz Technical University Davudpasa Campus. The coordinates of the stations in the test network were determined by conventional geodetic, classical RTK, VRS and FKP methods serviced by both Cors-TR and Iski Cors. The results were compared to the coordinates by the conventional method by using total station. The results showed a complex structure as the accuracy differs from one component to another such as in horizontal coordinates, Y components by CorsTR_VRS and Cors_TR_ FKP showed ‘best’ results while the same technique provided X components consistent accuracy with the Y component but less accurate than by real time kinematic (RTK). In vertical components, of all the techniques used for the h components, CorsTR_VRS showed ‘best’ accuracy with three outliers.